A chest lump in a toddler – a report on approach in primary care - Che Ku Mamat, Muhammad Yassir; Shalihin, Mohd Shaiful Ehsan (UniKL Royal College of Medicine Perak, 2025)
A chest wall lump is an uncommon clinical finding often indicative of underlying pathology, including abscesses, trauma, congenital deformities, or malignancy. Therefore, a systematic approach to evaluation is crucial. One such rare congenital anomaly is a bifid rib, typically asymptomatic but occasionally presenting as a palpable chest wall mass, potentially leading to unnecessary imaging or concern. Additionally, bifid ribs may coexist with syndromic conditions such as Gorlin syndrome, which is linked to an increased risk of skin malignancies. We present a rare case of a 4-year-old girl with a firm, immobile swelling in the right anterior chest wall, raising a diagnostic dilemma regarding the necessity of imaging. Given the clinical characteristics, radiological assessment was pursued, and a plain chest radiograph confirmed the diagnosis of a right bifid rib. This case highlights the importance of careful clinical evaluation and judicious use of imaging to avoid over-investigation while ensuring accurate diagnosis. Furthermore, we propose an evidence-based algorithm for evaluating chest wall lumps in primary care settings to inform clinical decision-making.